The Voter and the Propagandistic Content on Facebook: Analysis of the Content and Perception of the Ecuadorian Voter - Gandhy Godoy-Guevara; Andrea Basantes-Andrade; Miguel Naranjo-Toro; David Ortiz-Dávila (Societies)
This research seeks to elucidate the influence of Facebook advertising content on voting decisions and public perceptions of candidates during the 2023 Imbabura elections, exploring both how citizens perceive such content and how it affects their voting behavior. A case study approach was employed, integrating content analysis through Atlas.ti and the application of factor analysis to survey interpretation. The findings revealed that specific content, such as memes, exerts a notable influence on the younger electorate. This influence is reinforced by communication strategies that emphasize the frequency and repetition of this content, although no direct correlation with key demographic variables was found. Furthermore, the study demonstrates that a communication strategy devoid of value content reduces social networks to mere information channels, akin to open television. In conclusion, the study emphasizes the necessity of digital communication strategies that prioritize the creation of valuable content for audiences, with the aim of fostering a more discerning and engaged electorate.